Evaluation of CT Perfusion in the Setting of Cerebral Ischemia: Patterns and Pitfalls - Lui, Y.W.; Tang, E.R.; Allmendinger, A.M.; Spektor, V. (American Journal of Neuroradiology, 2010)
SUMMARY: CTP has a growing role in evaluating stroke. It can be performed immediately following NCCT and has advantages of accessibility and speed. Differentiation of salvageable ischemic penumbra from unsalvageable core infarct may help identify patients most likely to benefit from thrombectomy or thrombolysis. Still, CTP interpretation can be complex. We review normal and ischemic perfusion patterns followed by an illustrative series of technical/diagnostic challenges of CTP interpretation in the setting of acute stroke syndromes. ACAanterior cerebral arteryAIFarterial input functionASPECTSAlberta Stroke Program Early CT ScoreCBFcerebral blood flowCBVcerebral blood volumeCTACT angiographyCTPCT perfusionDWIdiffusion-weighted imagingICAinternal carotid arteryMCAmiddle cerebral arteryMTTmean transit timeNCCTnoncontrast CTPETpositron-emission tomographySPECTsingle-photon emission CTTTPtime to peakVOFvenous output function